ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN JASA KEUANGAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012) - SE, M.Si, Ak, Rini Hidayah; Sulistiyo Adi, SE, Affan (Majalah Neraca, 2014)
This study aims to find empirical evidence on the factors that affect the timeliness of the financial statements of banking financial services company listed on the Indonesia Stock Exchange. The factors examined in this study is the debt to equity ratio, profitability, ownership structure, the quality of public accounting firms, liquidity, and firm age. This study used a sample of 54 banking financial services company that consistently listed in the Indonesia Stock Exchange 2010-2012 period were taken by using purposive sampling. These factors were then tested using logistic regression at a significance level of 5 percent. The result showed that the debt to equity ratio and liquidity affect the timeliness of financial reporting. However, profitability, ownership structure, the quality of public accounting firms, and firm age does not affect the timeliness of the financial statements of banking financial services company listed on the Indonesia Stock Exchange. Keywords : Timeliness, Debt to Equity Ratio, Profitabiltiy, Ownership Structure, The Quality of Public Accounting Firms, Liquidity, and Firm Age.